Aktivitas Ekstrak Batang Akar Laka (Dalbergia parviflora Roxb.) Terhadap Pertumbuhan Jamur Trichophyton rubrum - Amran Rexana Djumaty; Irwandi Irwandi; A.M. Muslihin (Journal of Pharmaceutical and Sciences, 2026)
Akar laka (Dalbergia parviflora Roxb.) is a traditional medicinal plant used by communities in North Maluku to treat various types of wounds and skin conditions; however, scientific research on the antifungal activity of this plant’s stem is still limited. This study aims to identify the content of secondary metabolites and evaluate the antifungal activity of akar laka stem extract against the growth of Trichophyton rubrum in vitro. This is a laboratory experimental study conducted using the maceration method with 95% ethanol as a solvent to obtain a concentrated extract, followed by phytochemical screening to identify the classes of secondary metabolites. Antifungal activity testing was performed using the disk diffusion method with extract concentrations of 5%, 10%, and 15%, with ketoconazole used as the positive control and aqua pro injection as the negative control. The results showed that from 200 grams of crude drug, 43 grams of concentrated extract were obtained with a yield of 21.5%. Phytochemical screening results indicated the presence of alkaloids, saponins, and tannins, while flavonoids were not detected. In the antifungal activity test, the extract did not form an inhibition zone at any of the tested concentrations against T. rubrum, whereas the positive control exhibited a very strong inhibition zone of 26.7 mm. Based on the research results, it can be concluded that the extract of the akar laka stem (D. parviflora Roxb.) contains several secondary metabolites but did not exhibit antifungal activity against T. rubrum at the tested concentrations.